Interreader Agreement of Liver Imaging Reporting and Data System on MRI: A Systematic Review and Meta‐Analysis - Kang, Ji Hun; Choi, Sang Hyun; Lee, Ji Sung; Park, Seong Ho; Kim, Kyung Won; Kim, So Yeon; Lee, Seung Soo; Byun, Jae Ho (Journal of magnetic resonance imaging, 2020)
Background Use of the Liver Imaging Reporting and Data System (LI‐RADS) is increasing, but the reported results for interreader agreement seem quite variable. Purpose To systematically determine the interreader agreement of LI‐RADS on magnetic resonance imaging (MRI) and to determine the sources of heterogeneity between the reported results. Study Type Systematic review and meta‐analysis. Subjects Fifteen original articles with 2968 lesions. Field Strength 1.5T and 3.0T. Assessment Two reviewers independently performed the data extraction. The reviewers identified and reviewed the original articles reporting the interreader agreement of LI‐RADS using MRI. Statistical Tests The meta‐analytic pooled intraclass correlation coefficient (ICC) for lesion size and kappa value (κ) for major features (arterial‐phase hyperenhancement [APHE], nonperipheral washout [WO], enhancing capsule [EC]) and LI‐RADS categorization (LR) were calculated using the random‐effects model. Sensitivity analysis and meta‐regression analysis were performed to explore the cause of study heterogeneity. Results The meta‐analytic pooled ICC of lesion size was 0.97 (95% confidence interval [CI], 0.94–1.00). Meta‐analytic pooled κ of APHE, WO, EC, and LR were 0.72 (95% CI, 0.62–0.82), 0.69 (95% CI, 0.60–0.78), 0.66 (95% CI, 0.58–0.74), and 0.70 (95% CI, 0.56–0.85), respectively. Substantial study heterogeneity was noted in all five variables (I2 ≥ 89.1%, P < 0.001). Study design, type, and clarity of blinding review were factors that significantly influenced study heterogeneity (P ≤ 0.05). Data Conclusion LI‐RADS demonstrated overall substantial interreader agreement for major features and the category on MRI, but showed heterogeneous results between studies. Level of Evidence 3 Technical Efficacy Stage 2 J. Magn. Reson. Imaging 2020;52:795–804.